An 11-week school-based 'health education through football programme' improves health knowledge related to hygiene, nutrition, physical activity and well-being-and it's fun! A scaled-up, cluster-RCT with over 3000 Danish school children aged 10-12 years old - Larsen, M. N.; Elbe, A.-M.; Madsen, M.; Madsen, E. E.; Oerntoft, C.; Ryom, K.; Dvorak, J.; Krustrup, P. (British Journal of Sports Medicine, 2021)
Objectives: Our large-scale cluster randomised controlled trial aimed to investigate the effects on health knowledge and enjoyment of an 11 week 'health education through football' programme for children aged 10-12 years old. Methods: 3127 Danish school children (49% girls) aged 10-12 years from a total of 154 schools located in 63% of the Danish municipalities (69 of 98) took part in the analysis. A 5:1 cluster randomisation was performed at school level for the intervention group (IG) or the control group (CG). The twice-weekly 45 min intervention was the '11 for Health in Denmark' programme, which includes health education, football drills and small-sided games. The health education element focused on hygiene, nutrition, physical activity and well-being. Outcomes: The participants completed a 34-item multiple-choice computer-based health knowledge questionnaire preintervention and postintervention. IG also evaluated whether the programme was enjoyable. Results: Between-group differences (p<0.05) were observed in overall health knowledge in favour of IG (+7.2% points, 95% CI 6.1% to 8.4%, effect size, ES:0.59), with similar effects for girls (+7.4% points, 95% CI 5.9% to 9.0%, ES:0.57) and for boys (+7.0% points, 95% CI 5.3% to 8.7%, p<0.05, ES:0.51). Marked between-group differences were observed in favour of IG, for health knowledge related to hygiene (IG vs CG:+13.9% points, 95% CI 11.1% to 16.7%, ES:0.53), nutrition (+10.3% points, 95% CI 8.5% to 12.1%, ES:0.53), physical activity (+5.9% points, 95% CI 4.1% to 7.7%, ES:0.36) and well-being (+4.4% points, 95% CI 2.7% to 6.1%, ES:0.28). Both girls and boys gave the programme moderate to high scores for enjoyment (3.6±1.0 and 3.7±1.1, respectively). Conclusion: Health education through sport, using the '11 for Health' model, was enjoyable for girls and boys aged 10-12 years old, and improved health knowledge related to hygiene, nutrition, physical activity and well-being.